An investigation of student engagement in a Malaysian public university - Teoh, Hee Chong; Abdullah, Maria Chong; Roslan, Samsilah; Mohd Daud, Shaffe (Elsevier, 2013)
This study aims to investigate the characteristics of student engagement in a local public university. Student engagement refers to the concept of “students learn from what they do in college” and has been in literature for more than 70 years. A survey form adapted from College Student Experience Questionnaire (CSEQ) was distributed to a total of 64 first and second year students. This study employed descriptive research design as to address the research objectives, namely to identify the characteristics of student engagement and to differentiate student background characteristics, including year of study and gender, of student engagement based on five indices. The results of the study indicated that students scored high intermediate on the level of student engagement. Further investigation on the five indices of student engagement revealed that students rated highest on “life-long learning” index, followed by the indices of “active learning”, “cooperation among students”, “experience with diversity” and lastly was “student-faculty interaction” index. While comparing the student engagement and its indices across year of study and gender, the empirical study revealed that there was no significant difference on year of study. However, females showed significantly more engagement than males. The same result applied for “active learning” and “experience with diversity” indices. As a result, some suggestions have been given to address the issues raised as to further enhance the “student-faculty interaction” and the solutions for relatively low engagement of male students.